Analyzing the Impact of Land Resource Dimension on Konjac (Amorphophallus onchophyllus) Yield and Land Suitability Criteria Using PLS-SEM and Boundary Line Methods In Gorontalo, Indonesia - Nurdin, Nurdin; Pembengo, Wawan; Adam, Echan; Moonti, Agustinus; Rahman, Rival; Suparwata, Dewa Oka; Angelia, Ika Okhtora; Azis, Muhammad Arief; Arsyad, Silviana; Dude, Suyono; Zakaria, Fauzan; Bagu, Fitria S.; Apriliani, Silvana; Mokoginta, Meity M.; Pade, Satriawati; Rajib, Md. Mijanur Rahman; Hakiman, Mansor (AGRIVITA Journal of Agricultural Science, 2026)
The current land suitability criteria for konjac are incomplete and fail to consider land dimensions and quality, which influence optimal yield. This research aims to develop criteria for konjac land suitability based on the dimensions, quality, and characteristics of selected land. In Gorontalo Province, Indonesia, 131 land units were surveyed to obtain data on the quality and characteristics. Selection of land dimensions, quality, and characteristics using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). Meanwhile, the optimum yield and distinguished land suitability criteria for konjac plants using the boundary line method. The results indicated that intrinsic and extrinsic dimensions determined the new land suitability criteria. In the intrinsic dimension, land quality was assessed based on root conditions, oxygen availability, nutrient availability, nutrient retention, and sodicity. For the extrinsic dimension, land quality only comprised temperature, water availability, land preparation, and erosion hazard. Land characteristics in the intrinsic dimension consisted of soil drainage, texture, bulk density, particle density, porosity, pH, organic C, CEC, base saturation, total N, available P, and exchangeable K. For the extrinsic dimension, land characteristics included slope, soil erosion, surface rocks, and rock outcrops. The highest optimum yield of konjac was 9.17 t/ha, and the lowest was 6.69 t/ha, respectively.